Business Planning : Minor Red Chord / Mohd Fahmezam Mat Noh ...[et al.] - Mat Noh, Mohd Fahmezam; Ja’afar, Mohamad Fuad; Kamalul Ariffin, Mohd Elyashaq; Abd Aziz, Azlan; Mhd Subri, Mhd Faiz (2010)
Name of our company is MINOR RED CHORD. Our company provide the music instruments such as guitar, bass, drum, keyboard, their spare part and provide studio for recording, jamming and music classes. As we know, there are a lot of industries in our country such as entertainment, economy, and agriculture and so on. Music industry is the most popular among the citizens in Malaysia, also across the world. Music industry also has its own benefit for the people where it can give people the music skills, knowledge, and attract them to involve in the music field. This company can bring benefits in upgrading music industry in our country and also bonuses for those who want to advances their music field especially. Our jobs are to make sure our customers satisfied with our selling and services. We allowed customers who are interested in making their own album and sing the song that they like